Phytochemical Profiling of Methanolic and Ethanolic Extracts of Pemphis acidula (J.R.Forst. & G.Forst.) Leaf using LC–MS/MS and GC–MS - Sakinah, Putri; Fathoni, Ahmad; Sinaga, Ernawati (Jurnal Kefarmasian Indonesia, 2025)
Pemphis acidula (J.R.Forst. & G.Forst.) is a mangrove species of the Lythraceae family widely distributed along the Indonesian coasts. Traditionally used for medicinal and cosmetic purposes, information on its phytochemical composition remains limited. Comprehensive chemical profiling is essential to elucidate its bioactive potential and development. This study aimed to identify, characterize, and compare the phytochemical and bioactive profiles of methanolic and ethanolic extracts of Pemphis acidula using LC–MS/MS and GC–MS to determine which solvent yields richer bioactive composition. Leaf samples were collected and authenticated at Herbarium Bogoriense (BRIN). The dried powders were extracted with methanol or ethanol by triple maceration for 24 hours, and filtrates were evaporated under reduced pressure. Crude extracts were analyzed using LC–MS/MS (UPLC-QTOF, ESI ±) and GC–MS; compound identification employed UNIFI software referencing the Waters Traditional Medicine Library and Wiley 275 database. The results showed that LC–MS/MS identified 25 compounds in methanolic and 49 in ethanolic extracts, while GC–MS detected 13 and 19 compounds, respectively, with quality matches ≥90%. These compounds comprised alkaloids, flavonoids, phenols, polyphenols, and terpenoids with antioxidant, anti-inflammatory, antibacterial, antiviral, and anticancer activities. Eleven non-volatile compounds were identified in both extracts, namely kaempferol-3-glucuronide, desmanthin, quercetin-3-O-α-D-glucuronide, quercetin-3-O-glucuronide 6″-methylester, ellagic acid, Z-ligustilide, melazolide A, cimicifugic acid B, vellerdiol, 5,6,7,7α-tetrahydro-4,4,7α-trimethyl-2(4H)-benzofuranone, and farnesyl acetate and seven volatile compounds were identified in both extracts, i.e. supraene, hexadecanoic acid methyl ester, loliolide, 9,12-octadecadienoic acid (Z,Z)-methyl ester, phytol, 9-octadecenoic acid, and tocopherol. In conclusion, Pemphis acidula extracts contain bioactive compounds with medicinal potential, and ethanol extract yielded a broader phytochemical profile than methanol’s.